Isolation and Reactivity of a Frustrated N‐Heterocyclic Carbene‐Borane. Issue 22 (17th October 2016) - Winkler, Andrea; Freytag, Matthias; Jones, Peter G.; Tamm, Matthias
Abstract : The synthesis of the frustrated carbene‐borane 4‐(9‐borabicyclo[3.3.1]nona‐9‐yl)‐1, 3‐di‐ tert ‐butylimidazolin‐2‐ylidene (6 ) was accomplished by deprotonation of the N ‐heterocyclic carbene (NHC) 1, 3‐di‐ tert ‐butylimidazolin‐2‐ylidene (1 ) at the 4‐position with n ‐butyllithium, followed by addition of 9‐chloro‐9‐borabicyclo[3.3.1]nonane (BBN‐Cl). The abnormal carbene‐borane adduct5, with the BBN‐Cl moiety at the 4‐position, was obtained from the reaction of1 with BBN‐Cl; however, its conversion into6 by treatment with K[N(SiMe3 )2 ] (potassium hexamethyldisilazide, KHMDS) was not achieved. The reactions of6 with the rhodium(I) complexes [Rh(COD)Cl]2 (COD = 1, 4‐cyclooctadiene) and [Rh(CO)2 Cl]2 afforded the complexes cis ‐[(6 )Rh(COD)Cl] (7 ) and cis ‐[(6 )Rh(CO)2 Cl] (8 ), with the latter allowing assessment of the σ‐donor/π‐acceptor properties of6 by IR spectroscopy. The reactivity of6 towards carbon dioxide, phenylacetylene and acetonitrile was studied, affording the labile adduct6· CO2 (9 ), whereas irreversible deprotonation and formation of the imidazolium phenylalkynylborate10 and the imidazolium cyanomethylborate11 was observed for PhCCH and CH3 CN. The molecular structures of5, 7, 8, 10, and11 were established by X‐ray diffraction analyses. Abstract :